Islamic architecture at the military threshold (Journal of the College of Basic Education, 2022)
Architecture in general and Islamic architecture in particular is the most prominent physical embodiment of the Arab-Islamic civilization, given the growing role of religious shrines as a natural extension of mosques.The renaissance began to know its way to the architecture of the shrines during the Umayyad and Abbasid eras.Our current research shed light on the architectural elements of Islamic architecture, which were used in the two holy shrines, adding an Islamic sanctity. The creativity of the Muslim architect emerged using arts, writings, and plant motifs mixed with geometric shapes.